ANALISIS RANTAI PASOK KOMODITI CABAI RAWIT DI PASAR BERSEHATI KOTA MANADO DI MASA PANDEMI COVID-19 - Riffani ., Kansil; Oktavianus ., Porajouw; Rine ., Kaunang (Sam Ratulangi University, 2021)
This study aims to analysis the supply chain mechanism for the cayenne pepper commodity in the Bersehati Market of Manado City during the Covid-19 pandemic. The data used in this study are primary data and secondary data. Primary data were obtained from observations, direct interviews, and interviews via WhatsApp with traders, consumers, and service providers in the Bersehati market. Secondary data were collected and obtained from employees in the Bersehati Market. The sampling method was carried out using the purposive sampling method (deliberately), namely selecting sources of information in the Bersehati Market. Number of sample used in this study was taken 10 respondents divided into 5 retailers, 3 consumers, 1 service provider, 1 market officer. This study uses descriptive analysis which is an analytical method used to determine the supply chain mechanism of cayenne pepper. The results showed that the supply chain mechanism for the cayenne pepper commodity in the Bersehati Market during the Covid-19 pandemic was related to product flows, financial flows and information flows that had differences in each flow. During the pandemic, there were 6 links that played an active role in the supply chain for the chili commodity at the Bersehati Market.